Coffee over the internet - Zhu, Yatao. (2008)
"Coffee Over the Internet", does not mean to drink or deliver coffee over the Internet, rather it implies "a dream" in the future. One day our dream may be realized. For example, all our home appliances can be connected to each other, to achieve control, to exchange information, to provide services and of course to connect to the Internet. And all this should happen without human intervention or administration. In fact, promising standards are merging at an accelerated speed. With current technology, what can we do about existing appliances? I hope this project provides part of the answer at least.